TMIC-27. GLUTAMATERGIC NEURON-GLIOMA SYNAPSES DRIVE BRAIN TUMOUR PROGRESSION. (11th November 2019) - Venkataramani, Varun; Tanev, Dimitar; Strahle, Christopher; Studier-Fischer, Alexander; Fankhauser, Laura; Kessler, Tobias; Losada Perez, Maria; Körber, Christoph; Kardorff, Markus; Ratliff, Miriam; Xie, Ruifan; Horstmann, Heinz; et al.
Abstract: A network of communicating tumour cells established by tumour microtubes (TMs) is supposed to mediate relevant aspects of progression and resistance of incurable gliomas. Moreover, neuronal activity has been shown to foster malignant behavior of glioma cells by non-synaptic paracrine and autocrine mechanisms. Here, we report an unexpected direct communication channel between neurons and glioma cells in multiple disease models as well as in astrocytomas and glioblastomas (GBs) of adult patients: functional bona fide chemical synapses formed between presynaptic neurons and postsynaptic glioma cells. These neurogliomal synapses (NGS) show a typical synaptic ultrastructure, are located on TM networks, and produce depolarizing postsynaptic currents mediated by glutamate receptors of the AMPA subtype. AMPA-type glutamate receptors (AMPAR) are expressed by a molecularly and morphologically distinct subpopulation of network-integrated glioma cells. Increased neuronal activity under epileptic conditions ex vivo or neuronal optogenetic stimulation in vivo enhanced, while general anesthesia diminished synchronized calcium transients in TM-connected glioma networks. Accordingly, anesthesia reduced invasiveness of TM-positive tumour cells in mice. Genetic perturbation of AMPAR or chronic AMPAR inhibition by perampanel decreased glioma invasion and proliferation in mice and deletion of GluRII in Drosophila glioma increased survival. These findings reveal a hitherto unappreciated direct synaptic communication between neurons and glioma cells that appears relevant for brain tumour biology, implying new avenues for glioma treatment.